2016
DOI: 10.1038/bmt.2016.142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high-risk amino-acid substitutions in hematopoietic cell transplantation: a challenging task

Abstract: Allogeneic hematopoietic cell transplantation (HCT) offers the potential to cure hematologic malignancies. Absent an HLA matched donor, HLA mismatched unrelated donors may be used although risks of graft-versus-host disease (GvHD) and treatment related mortality (TRM) are higher. Identification and avoidance of amino acid substitutions and position types (AASPT) conferring higher risks of TRM and GvHD would potentially improve the success of transplantation from single HLA mismatched unrelated donors. Using ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Different studies investigated the possible use of AI methods and tools to tackle this challenge. Marino et al [ 17 ] identified 19 amino acid substitutions related to at least one bad outcome following HCT using random forest and logistical regression methods. These included overall survival, treatment-related mortality, incidence of graft-versus-host disease (GVHD), etc.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies investigated the possible use of AI methods and tools to tackle this challenge. Marino et al [ 17 ] identified 19 amino acid substitutions related to at least one bad outcome following HCT using random forest and logistical regression methods. These included overall survival, treatment-related mortality, incidence of graft-versus-host disease (GVHD), etc.…”
Section: Resultsmentioning
confidence: 99%
“…ADT technique was used in four of the reviewed studies where it was used primarily to predict survival/death and relapse post-HSCT [17,24,25,27]. ADT outperformed RF model in one study [16,20,24,26,35,36,40]. Finally, logistic regression was used in six of the primary studies as a comparator technique, but it did not outperform any of the other ML techniques.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies [19,20] that applied ML techniques to identify specific genes responsible for relapse in patients undergoing HSCT. Ritari et al [19] performed a genomic-wide-sequencing of active immunoregulatory regions, whole exome, and MHC regions on 151 HSCT recipients with HLA matched donors.…”
Section: Post-hsct Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of ML and DL studies in HCT are for prognostication, but multiple studies have tried to tackle other problems, including pre-transplant patient’s selection. Donor/recipient and transplantation characteristics were used to create algorithms to improve pre-transplant match results [ 43 , 44 ]. Nonetheless, AI/ML is complex and dependent on multiple factors; thus, some algorithms had suboptimal accuracy or failed validation [ 43 , 45 ].…”
Section: And DL In the Diagnosis Of Hematological Diseasesmentioning
confidence: 99%